Scaffolding one Thai youth’s drawing toward resilience - Catherine Ann Cameron (2018)
© The Author(s) 2014. Drawings have been used extensively to explore the psychosocial development of children and youth. Focusing on the drawings of one thriving migrant Thai adolescent, this case study employs multiple sources of data from this youth to ground an integrated interpretation of his resilient processes in ecological context. Our participant, ‘Pond’, had recently relocated to northern Thailand with his father. Employing reflective interviews with the teenager about his experiences, his sketchbooks and a filmed ‘day in his life,’ we identified ‘promotive’ factors contributing to his well-being in the context of strong familial support. During his filmed day, we observed him drawing for one uninterrupted hour, the products of which he proudly shared with his artist father as well as the researchers. His sketchbook graphic endeavors included traditional Thai representations, pop-cultural sketches and cartooning, bridging the worlds he navigates as he adapts to his new domicile. Pond’s drawing activities and reflections on them confirm his sense of responsibility, self-confidence, positive affect in familial connection and his striving for social inclusion. His use of pictorial language reveals his cultural values and their potential for enhanced thriving. Pond affirmed that his artistic transactions are sources of strength to him in his migratory transition.